PENGARUH KEBIJAKAN PEMERINTAH, KUALITAS PERUMAHAN, LOKASI, PROMOSI DAN KEMUDAHAAN PEMBIAYAAN TERHADAP KINERJA PEMASARAN RUMAH SUBSIDI DI DESA NAMO BINTANG KEC. PANCUR BATU - Josi Renaldy Ginting; Isnen Fitri; Yeni Absah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the influence of government policy, housing quality, location, promotion, and financing ease on the marketing performance of subsidized housing in Namo Bintang Village, Pancur Batu District. The method used is an associative method with a quantitative approach, aiming to examine the relationship between variables in a study population of 300 respondents, using a sample of 171 respondents. Data analysis techniques used were multiple linear regression analysis, coefficient of determination tests, F tests, and t tests. The results of the study indicate that government policy, housing quality, location, promotion, and ease of financing simultaneously have a positive and significant effect on marketing performance, with a p-value of 0.000 < 0.05. The determination test revealed that government policy, housing quality, location, promotion, and ease of financing influenced marketing performance by 27.7%, with the remaining 72.3% being explained by other variables not specifically examined in this study, such as price and advertising.